2020
DOI: 10.4317/jced.56715
|View full text |Cite
|
Sign up to set email alerts
|

Accessory submaxillary gland: Two new case reports and a literature review

Abstract: Background The accessory submaxillary gland is a very uncommon anatomical variant, and incidence in the general population has not yet been quantified. The presence of pathology in these glands is rarer still, thus often going unnoticed. Material and Methods We describe two accessory submaxillary gland cases, one asymptomatic and the other with chronic sialadenitis in the main and accessory gland caused by sialolithiasis. Although our diagnosis was by computerized tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Our review of the literature identified reports of variation in anatomy of the submandibular gland to be rare. Fewer than 15 cases of accessory submandibular glands have been reported in our review of the literature, whereas accessory lobes to the parotid gland are common and have been in 32.1% of cases examined [1 , 2] .…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Our review of the literature identified reports of variation in anatomy of the submandibular gland to be rare. Fewer than 15 cases of accessory submandibular glands have been reported in our review of the literature, whereas accessory lobes to the parotid gland are common and have been in 32.1% of cases examined [1 , 2] .…”
Section: Discussionmentioning
confidence: 75%
“…Two case reports have utilized MR sialography to identify accessory submandibular glands [2 , 3 , 8] . However, in both instances, there was unilateral duplication of the submandibular gland with an accessory duct joining the main submandibular duct distal to the papilla.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations